Magnetic Resonance Imaging Reveals Distinct Roles for Tissue Transglutaminase and Factor XIII in Maternal Angiogenesis During Early Mouse Pregnancy. Issue 8 (August 2019) - Cohen, Gadi; Hadas, Ron; Stefania, Rachele; Pagoto, Amerigo; Ben-Dor, Shifra; Kohen, Fortune; Longo, Dario; Elbaz, Michal; Dekel, Nave; Gershon, Eran; Aime, Silvio; Neeman, Michal
Abstract : Objective: The early embryo implantation is characterized by enhanced uterine vascular permeability at the site of blastocyst attachment, followed by extracellular-matrix remodeling and angiogenesis. Two TG (transglutaminase) isoenzymes, TG2 (tissue TG) and FXIII (factor XIII), catalyze covalent cross-linking of the extracellular-matrix. However, their specific role during embryo implantation is not fully understood. Approach and Results: For mapping the distribution as well as the enzymatic activities of TG2 and FXIII towards blood-borne and resident extracellular-matrix substrates, we synthetized selective and specific low molecular weight substrate analogs for each of the isoenzymes. The implantation sites were challenged by genetically modifying the trophoblast cells in the outer layer of blastocysts, to either overexpress or deplete TG2 or FXIII, and the angiogenic response was studied by dynamic contrast–enhanced-magnetic resonance imaging. Dynamic contrast–enhanced-magnetic resonance imaging revealed a decrease in the permeability of decidual vasculature surrounding embryos in which FXIII were overexpressed in trophoblast cell. Reduction in decidual blood volume fraction was demonstrated when either FXIII or TG2 were overexpressed in embryonic trophoblast cell and was elevated when trophoblast cell was depleted of FXIII. These results were corroborated by histological analysis. Conclusions: In this study, we report on the isoenzyme-specific roles of TG2 and FXIII during the early days of mouse pregnancy and further reveal their involvement in decidual angiogenesis. Our results reveal an important magnetic resonance imaging-detectable function of embryo-derived TG2 and FXIII on regulating maternal angiogenesis during embryo implantation in mice.Visual Overview: An online visual overview is available for this article. Abstract : Supplemental Digital Content is available in the text.